Social-Cultural Values Embodied in the film of Bumi Manusia - Razali , Geofakta; Silvira, Melva; Marlis, Andree; Marly, Neil (Journal International Dakwah and Communication, 2022)
The purpose of this study is to find the values conveyed in the film of Bumi Manusia regarding the social values of the Javanese people and to find out the cultural values conveyed in the film of Bumi Manusia regarding Javanese society. This research is included in qualitative research. The type of research that researchers use is research (documentary research). The data collection technique carried out is to identify several images and dialogues contained in shots and scenes which depict the social and cultural values of the Javanese people. By using descriptive methods and content analysis methods, namely analyzing scenes, and character dialogues based on social and cultural values. The results of this study are expected to be able to answer research questions about social and cultural values in a film and later can be scientifically accounted for and provide advice to young filmmakers in their work.